2015
DOI: 10.1007/s00442-015-3418-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, behavior, and condition of herbivorous fishes on coral reefs track algal resources

Abstract: Herbivore distribution can impact community structure and ecosystem function. On coral reefs, herbivores are thought to play an important role in promoting coral dominance, but how they are distributed relative to algae is not well known. Here, we evaluated whether the distribution, behavior, and condition of herbivorous fishes correlated with algal resource availability at six sites in the back reef environment of Moorea, French Polynesia. Specifically, we tested the hypotheses that increased algal turf avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 79 publications
4
36
0
Order By: Relevance
“…that herbivorous fishes (primarily parrotfishes) and not sea urchins were responsible for the control of macroalgae on the fore reef of Moorea. One reason why herbivory pressure on the fore reef remained so far above our estimated macroalgae tipping point was a rapid increase in biomass of herbivorous fishes that occurred following the perturbation, likely in response to increased food availability35404950. However, given that we found comparatively little herbivory was required to keep macroalgae suppressed, it could well be the case that even the lower, pre-disturbance herbivory pressure would have been sufficient to keep fleshy macroalgae suppressed.…”
Section: Discussionmentioning
confidence: 77%
“…that herbivorous fishes (primarily parrotfishes) and not sea urchins were responsible for the control of macroalgae on the fore reef of Moorea. One reason why herbivory pressure on the fore reef remained so far above our estimated macroalgae tipping point was a rapid increase in biomass of herbivorous fishes that occurred following the perturbation, likely in response to increased food availability35404950. However, given that we found comparatively little herbivory was required to keep macroalgae suppressed, it could well be the case that even the lower, pre-disturbance herbivory pressure would have been sufficient to keep fleshy macroalgae suppressed.…”
Section: Discussionmentioning
confidence: 77%
“…Decreases in herbivore abundance despite adequate food supply may be a result of differences in algal quality, not quantity. Studies in shallow systems have found that herbivore patchiness is strongly correlated with differences in algal productivity (Russ 2003;Tootell and Steele 2016). Although currently untested, it is plausible that productivity of turf and macroalgal resources decreases with depth given the low light availability at mesophotic depths, which could then account for observed declines in herbivorous fishes with depth.…”
Section: Discussionmentioning
confidence: 98%
“…Since nominally herbivorous fish track benthic characteristics and algal resources spatially (Russ et al. , Tootell and Steele ), they could respond to temporal changes in benthic community structure and algal cover. Benthic community structure was therefore quantified by recording the presence of 21 broad benthic categories (Appendix ) every 50 cm along 50 m point‐intercept transects ( n = 4 per site).…”
Section: Methodsmentioning
confidence: 99%
“…We focused on individuals larger than 10 cm in TL and thus capable of consuming the smallest of potential target prey species considered here (i.e., damselfish; Madin et al 2012). Since nominally herbivorous fish track benthic characteristics and algal resources spatially (Russ et al 2015, Tootell andSteele 2016), they could respond to temporal changes in benthic community structure and algal cover. Benthic community structure was therefore quantified by recording the presence of 21 broad benthic categories (Appendix S6: Table S6) every 50 cm along 50 m pointintercept transects (n = 4 per site).…”
Section: Data Collectionmentioning
confidence: 99%